2007
DOI: 10.1128/jvi.01427-07
|View full text |Cite
|
Sign up to set email alerts
|

SH3 Binding Motif 1 in Influenza A Virus NS1 Protein Is Essential for PI3K/Akt Signaling Pathway Activation

Abstract: Recent studies have demonstrated that influenza

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
145
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 118 publications
(157 citation statements)
references
References 40 publications
(49 reference statements)
7
145
0
1
Order By: Relevance
“…In a previous report, we showed that WT virus led to caspase-9 phosphorylation, whereas PR8-SH3-mf-1 virus did not (Shin et al, 2007a). Taking our data together, we propose the following model of how the PI3K/Akt pathway regulates apoptosis during influenza A virus infection (Fig.…”
Section: Discussionmentioning
confidence: 51%
See 4 more Smart Citations
“…In a previous report, we showed that WT virus led to caspase-9 phosphorylation, whereas PR8-SH3-mf-1 virus did not (Shin et al, 2007a). Taking our data together, we propose the following model of how the PI3K/Akt pathway regulates apoptosis during influenza A virus infection (Fig.…”
Section: Discussionmentioning
confidence: 51%
“…We previously reported that mutant virus PR8-SH3-mf-1 carrying three mutations (P162A/P164A/ P167A) in NS1 failed to induce PI3K/Akt activity but induced more severe apoptosis than the WT virus (Shin et al, 2007a). The current study was initiated to define how the PI3K/Akt pathway regulates influenza A virus-induced apoptosis.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations